PENGARUH KONTEN MARKETING DAN INFLUENCER MARKETING TERHADAP MINAT BELI - Erika Oktavia; Onsardi Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of content marketing and influencer marketing on consumers’ purchase intention at Flo Distro Bengkulu. This research employs a quantitative approach using a survey method, in which data were collected through the distribution of questionnaires to consumers of Flo Distro Bengkulu. The data analysis techniques used include validity testing, reliability testing, multiple linear regression analysis, t-test, and F-test with the assistance of statistical software. The results show that, partially, content marketing has a positive and significant effect on consumers’ purchase intention, as indicated by a significance value of 0.001 < 0.05 and a t-value greater than the t-table value. Influencer marketing also has a positive and significant effect on purchase intention, with a significance value of 0.004 < 0.05 and a t-value greater than the t-table value. Furthermore, simultaneously, content marketing and influencer marketing have a significant effect on consumers’ purchase intention, as indicated by the F-value being greater than the F-table value and a significance value of 0.000 < 0.05. These findings indicate that attractive, informative, and consistent marketing content, as well as the use of influencers with high credibility and congruence with the brand image, can increase consumers’ purchase intention. Therefore, based on the research results, it can be concluded that the implementation of content marketing and influencer marketing contributes to increasing consumers’ purchase intention at Flo Distro Bengkulu. Keywords: Content Marketing, Influencer Marketing, Purchase Intention, Social Media, Flo Distro Bengkulu.